(untitled) (The Peerian Journal, 2022)
This paper presents the results of the study of mathematical modeling methods to solve the problem of automated management of the labor market. The results of the study are summarized using brief conclusions. In the optimization of the labor market, a differential genetic algorithm was studied and an algorithm for determining the patterns that best represented the population target function was developed.